Interfaces. - Haber, Alicia; Maggio, Nelson di (Montevideo : Goethe-Institut, 2001)
Aguerre, Enrique ; Alvarez Cozzi, Fernando ; Amato, Guillermo ; Bentancur, Patricia ; Branca, Nicolas ; Diaz, Bettina ; Fornasari, Eduardo ; Goldwasser, Gerardo ; Mackern, Brian ; Martinez Portillo, Alcides ; Rosales, Juliana ; Sagradini, Mario ; Sastre, Martin ; Seoane, Ariel ; Sequeira, Alejandro ; Soto, Jorge Francisco ; Tavella, Santiago ; Zinno, Alvaro
biog. [1 p.]
Spaans
Interfaces, Goethe-Institut, Montevideo, Abril - Mayo de 2001
boek